2016
DOI: 10.1155/2016/1238392
|View full text |Cite
|
Sign up to set email alerts
|

Black Colouration of the Knee Articular Cartilage after Spontaneously Recurrent Haemarthrosis

Abstract: Mild discolouration of the articular cartilage is known to gradually occur during aging. However, pathological tissue pigmentation is occasionally induced under several specific conditions. In the present case, we performed total knee replacement in a patient with recurrent haemarthrosis. However, during the operation, we observed severe black colouration of the knee articular cartilage, due to the deposition of hemosiderin and lipofuscin. To our knowledge, this is the first report of severe cartilage pigmenta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 12 publications
0
7
0
Order By: Relevance
“…Furthermore, it may have a chemically reactive surface that can disturb cellular metabolism. Lipofuscin has been reported to accumulate in natural cartilage [ 38 ]. Although the effects of lipofuscin on cartilage metabolism are unknown, culture conditions that produce no lipofuscin should be used for repairing cartilage damage.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, it may have a chemically reactive surface that can disturb cellular metabolism. Lipofuscin has been reported to accumulate in natural cartilage [ 38 ]. Although the effects of lipofuscin on cartilage metabolism are unknown, culture conditions that produce no lipofuscin should be used for repairing cartilage damage.…”
Section: Introductionmentioning
confidence: 99%
“…Pigmented villonodular synovitis is a proliferative disorder of the synovium with locally aggressive nature, and its etiology is unclear, although neoplasm, recurrent hemorrhage, and trauma have been reported as possible causes. 8,9 To our knowledge, there are no reports of severe articular surface, synovial, and meniscal pigmentation in patients with PVNS; however, certain conditions have been reported to cause severe articular cartilage and meniscal pigmentation abnormalities in patients, such as alkaptonuria (ochronosis) and use of antibiotics and drugs such as levodopa and methyldopa. [1][2][3][4][5][6][7] In 2016, Matsumoto et al reported black discoloration of the knee articular cartilage after spontaneous recurrent hemarthrosis in a patient and concluded that hemosiderin and lipofuscin accumulation due to recurrent hemarthrosis might increase black pigmentation of joint cartilage.…”
Section: Case Reportmentioning
confidence: 99%
“…[1][2][3][4][5][6][7] In 2016, Matsumoto et al reported black discoloration of the knee articular cartilage after spontaneous recurrent hemarthrosis in a patient and concluded that hemosiderin and lipofuscin accumulation due to recurrent hemarthrosis might increase black pigmentation of joint cartilage. 9 They roll outed specific condition by histopathological examination. 9…”
Section: Case Reportmentioning
confidence: 99%
“…Alkaptonuria is a rare autosomal recessive metabolic disorder caused by a deficiency in homogentisic acid oxidase, resulting in the accumulation of homogentisic acid in collagenous structures [1] , [2] . This causes the classic clinical triad of homogentisic aciduria (blackening of the urine after standing when oxidized or alkalinized); eumelanin-like pigmentation of the skin, sclera, cartilages, and other organs; and degenerative ochronotic arthropathies commonly appearing in the fourth decade of life [3] .…”
Section: Introduction and Importancementioning
confidence: 99%
“…However, in some cases such as ochronotic arthritis, pathological tissue pigmentation can occur. Matsumoto et al reported black discoloration in the knee articular cartilage due to deposition of hemosiderin and lipofuscin caused by recurrent hemarthrosis [1] , [2] . In this case report, we present a case of ochronotic arthritis managed by TKR.…”
Section: Introduction and Importancementioning
confidence: 99%